(untitled) (Research, Society and Development, 2026)
This study aimed to review the literature regarding the main aspects related to bisphosphonates (BFs) and medication-related osteonecrosis of the jaw (MRONJ), addressing pharmacological characteristics, mechanisms of action, pathophysiology, clinical manifestations, staging, and prevention and management strategies. A literature review was conducted based on scientific articles indexed in international databases (PubMed, Google Scholar, LILACS e SciELO), including guidelines from the American Association of Oral and Maxillofacial Surgeons. Our findings highlighted that BFs, particularly nitrogen-containing agents, present high affinity for bone tissue and significantly suppress osteoclastic activity, potentially impairing bone remodeling and local vascularization. The MRONJ presents a multifactorial etiopathogenesis and is frequently associated with invasive dental procedure. Clinical staging plays a fundamental role in therapeutic decision. Prevention through prior dental assessment and continuous follow-up is the most effective strategy to reduce disease incidence. The MRONJ is a relevant complication of BFs therapy, requiring integrated action between the dentist and medical team, emphasizing preventive dental care and individualized conservative management.